GAGACHAT AS ONE OF THE COMMUNICATIVE FORMS OF NETWORK FOLKLORE ON THE EXAMPLE OF LADY GAGA’S INSTAGRAM ACCOUNT - Elena Aleksandrovna Yukhmina; Nadezhda Valerevna Obvintseva (Sovremennye Issledovaniâ Socialʹnyh Problem, 2019)
Purpose. The article considers “virtual flashmob” (on the basis of comments to an English post) as one of the communicative forms of network folklore in order to describe its functions and forms of manifestation as well as to give a classification of the comments into thematic groups and analyze their linguistic peculiarities. Сomments of active users of the social network Instagram constitute the empirical base of this study. The theoretical base relies on works of Russian and foreign researchers of virtual folklore Nathan Chandler, Simon J. Bronner, Trevor J. Blank, V.P. Rukomoinikova, Yu.M. Sokolov, A.S. Kargin, etc.